Nuova antologia militare : rivista interdisciplinare della Società italiana di storia militare - Alegi, Gregory; Società italiana di storia militare (Gruppo editoriale Tab S.r.l, 2020)
"Nuova antologia militare" (NAM) ideally refers to "Antologia militare," the oldest Italian military journal, published in Naples by Antonio and Girolamo Calà Ulloa between 1835 and 1846. NAM wants to be an interdisciplinary and international forum for the historical study of conflicts, war and the military.
Keywords: Military history : Periodicals; Military history; Italy : History, Military : Periodicals; Italy